STUDY ON COMPARISON BETWEEN FASTING AND RANDOM LIPID LEVELS IN TYPE 2 DIABETES MELLITUS IN A TERTIARY CARE CENTRE - Suresh K; Sathiya Sai Kiruba KB; S. Kasipandian; M. Priyatharshini (The Bioscan, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic condition linked to increased cardiovascular risk, primarily due to postprandial hyperglycemia and hypertriglyceridemia. Aim: To compare fasting and random lipid profiles in diabetic patients and assess the clinical utility of random lipid testing. Methods: A case-control study was conducted at a Tertiary Care Center in Puducherry involving 110 diabetic patients and 110 non-diabetic controls. Fasting lipid samples were taken after 8 hours of fasting, and random samples were collected 2 hours post-meal. Results: Significant differences in all lipid parameters (triglycerides, LDL-C, VLDL-C, HDL-C, total cholesterol) were observed between diabetics and non-diabetics, in both fasting and random states. Among diabetics, only triglyceride levels differed significantly between fasting and random tests (p < 0.001), while other lipid values showed no significant variation. Conclusion: Random lipid profiling may be a practical alternative to fasting tests for diabetic patients, but further large-scale studies are needed for validation. KEYWORDS Type 2 Diabetes Mellitus, fasting lipid profile, random lipid profile